Exploratory Study Work Place Ostracism and Counter Productive Work Behavior among Nurses a. A Qualitative Exploratory Study - Razia Sultana, Muhammad Afzal, Kabir Ozigi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Human capital is the vital resource of any organization. The perceived inclusion of employees within the organization leads to positive employee outcomes such as psychological health, job satisfaction, commitment, and productivity. Whereas, on the other hand employee’s exclusion or ignorance at workplace, gives rise to negative employee outcomes in the form of counter productive work behavior. In the last decade, the concept of workplace mistreatment became the center of attention in health care research in general and specifically in Pakistan. Objectives: The aims and objective of current study was to explore the perception of nurses regarding workplace ostracism and counterproductive work behaviors at tertiary health care sector. Study Design: A qualitative descriptive design was used for this study. Methodology: A qualitative approach was adopted, and 12 semi-structured interviews from the staff nurses from tertiary health care hospital were conducted. The transcribed interviews were coded, and an inductive thematic analysis was used to generate themes and sub-themes. Results: The study findings depicted six behaviors, i.e. biased treatment, exclusion from formal and informal interactions, interpersonal alienation, delayed sharing or hiding of knowledge, lack of work-related, social and emotional support constituted the acts of workplace ostracism in hospital setting. The psychological well-being of nurses suffered in terms of negative emotions, reduced job, career and life satisfaction in their work and family life. There is more negative outcome of workplace ostracism as compare to positive one. This negative outcome regards as counterproductive work behavior and in depth, exploration reveals its meaning, causes and consequences on both individual and organizations. Practical Implications: This exploratory study focuses on workplace ostracism and counterproductive work behavior among nurses in a tertiary healthcare setting. The study highlights the negative impact of workplace ostracism on the psychological well-being and work-related outcomes of nurses, and emphasizes the need for creating inclusive work environments that promote positive employee outcomes. Conclusion: This study found six exclusionary behaviors, i.e. biased treatment, exclusion from formal and informal interaction, interpersonal alienation, delayed sharing or hiding of knowledge, lack of work related, social and emotional support that constituted the acts of ostracism in health sector. In addition, this study also explores the causes of ostracism as jealousy, envy, ethnic, political and union discrimination. Besides, it was found that workplace ostracism. Keywords: Workplace ostracism, Counterproductive work behavior, Nurses, Psychological well-being, qualitative, Contextual factors.